Encysted Hydrocele of Canal of Nück - Mohammed Babakir-Mina (Kurdistan Journal of Applied Research, 2016)
The canal of Nuck is analogous to a patent processus vaginalis in a male, which normally loses its communication to the peritoneal cavity within the first year of life. Failure of obliteration of this tract can result in a hydrocele. We present a case of 38 years old lady referred to our surgical unit from Gynecologist as left obstructed femoral hernia. A fluid filled sac (Encysted Hydrocele of Canal of Nück) with small indirect inguinal hernia.